Prevalence of lip sucking amongst 6-9-years old children - Decruz, Ashley Ann; Runkat, Jakobus; Hidayat, Syarief (Universitas Padjadjaran, 2013)
Oral habits in children are a common problem faced in the society. Lip sucking is one of such habit. Often overlooked, persistent lip sucking can bring upon deleterious effects upon the child’s dentition. This research was aimed to identify the signs of lip sucking amongst 6-9 years old children. The research was descriptive using the survey technique and was conducted at Dental Hospital of Faculty of Dentistry Universitas Padjadjaran, Bandung, through observation for signs of lip sucking and filling up a survey form. A total of 100 children were examined in this research. From 100 children, 44 of them were identified to have at least one sign of lip sucking with 11 (25%) children were aged 6 years old, 8 (18%) children were aged 7 years old, 11 (25%) children were aged 8 years old and as much as 14 (32%) children aged 9 years old. The remaining 56 children examined were not found to manifest any signs of lip sucking. Based on the study can be concluded that the prevalence of lip sucking was 44%.